Why should we care about care? Supply and Demand Assessment of Care Services in Georgia : A Mixed Methods Study - World Bank (World Bank, Washington, DC, 2019)
Only 58 percent of Georgian women ages 15 and above participate in the labor market, a slightly higher share than the Europe (51 percent) and Organisation for Economic Co-operation and Development (OECD) (51.3 percent) average but 20 percentage points lower than the share among men in the country. Moreover, the gender gap in labor force participation has been constant and around 18 to 20 percentage points over the last decade. Married women living in households with children under age six are at a higher disadvantage in the labor market; only 50 percent of them participate in the labor force compared to 84 percent of men with similar characteristics.The conflicting demand on women’s time for care and work activities represents a fundamental barrier to economic participation and generates a vicious circle of low labor market attachment and prominence of the care provider role that leads to increased vulnerability and gender-based inequalities. About 60 percent of working-age women not looking for a job in Georgia cite family responsibilities as the main reason (the share is 67 percent among married ones). In the case of men, this percentage is 21 percent. Georgia cannot afford to underutilize a large share of women whose lifetime productivity in the labor market is currently reduced by informal and at-home care provision. In fact, for Georgia, it has been estimated that differences in labor market activity rates between men and women amount to potential economic losses in gross domestic product per capita of approximately 11 percent (Cuberes and Teignier 2016a, 2016b). Policy options to appropriately address the challenges identified in this note include the expansion ofpublicly and privately provided childcare centers in both urban and rural areas, establishment ofeducation and accreditation programs to prepare caregivers and care entrepreneurs, development of aplan to increase quality of services with attention to costs, and design of eldercare system considering the impacts on care recipients, the active aging promotion objective of age-related policies, as well as the impacts on informal and family care providers and their ability to contribute to sustained economic growth.